American Economic Association Universal Academic Questionnaire Summary Statistics - Scott, Charles E; Siegfried, John J (American Economic Review, 2012)
American Economic Association Universal Academic Questionnaire Summary Statistics by Charles E. Scott and John J. Siegfried. Published in volume 102, issue 3, pages 631-34 of American Economic Review, May 2012